Codeswitching online: a case study of a bilingual online maths programme for grade 7 learners in Diepsloot, Johannesburg - Von Witt, Nathalia Jane (Rhodes University, Faculty of Humanities, School of Languages, 2016)
There is an education crisis in South Africa. Mathematics and literacy are at the forefront of the problem, as particularly evidenced by Annual National Assessment results (Department of Basic Education, 2014; Spaull, 2014). This research is motivated by the unequal access to quality learning which stems from learners learning through a poorly-understood second language with little to no cognitive academic language proficiency. The vast majority of South African learners learn through their second language, English, from Grade 4 onwards. English is the language of South Africa's political economy and is a global lingua franca; however, the understanding of concepts and content learnt at school is vital if one is to have any hope of putting one's English to good use. This research aimed to find a way to equip learners both with English proficiency and mathematical understanding simultaneously. This was done by implementing and evaluating an experimental bilingual course in an existing mathematics programme in the township of Diepsloot in Johannesburg, South Africa. This research used design-based research methodology, using both qualitative and quantitative research methods. This methodology was chosen as it allows theory and practice to intersect in a real-life setting, and for the successes and shortcomings of this intersection to be evaluated. This study encompasses both the evaluation and creation of the bilingual online mathematics course. The course is made bilingual through the creation of bilingual videos with the use of translanguaging and the creation of a bilingual glossary of terms. The videos were created using a translanguaging 'model' informed by theories of basic interpersonal communication skills and cognitive academic language proficiency (Cummins, 1981), common underlying proficiency (Cummins, 1991), codeswitching (Setati, 1998; Ncoko et al., 2000) and translanguaging (Makalela 2015; Creese and Blackledge, 2010a). The aim of this research was to create a successful translanguaging model which facilitates learners' ability to conceptualise in their first language and then discuss and understand the concept in their second language.
Keywords: Uncatalogued